POETRY TRANSLATION: THE CORRELATION BETWEEN THE LANGUAGES AND POETIC SYSTEMS - Aidakhon M. Bumatova (Zeta Repository, 2023)
When thinking about literature, it is emphasized that the work tools of the stone mason are stone and tools, the work tools of the painter are paper, colors and brushes, and the work tools of the writer are words. Continuing this logic, it can be noted that the primary working tool of any translator is the text created in the original language. Therefore, the quality of the resulting translated text depends not only on the professional skills of the translator, but also on the primary characteristics of the original text. This article focuses on the main types of images and imagery that are presented in the texts of ghazals and rubaiyat composed in the medieval ages by famous poetry of Islamic oriental world.